The Effect of a 20-Hour Baby-Friendly Hospital Initiative Training Program on Nurses’ Breastfeeding Knowledge, Attitudes and Confidence, in a Tertiary Hospital in Singapore - Fok, Doris; Chang, Hsin Fang; Meng, Ling Yan; Ng, Yvonne Peng Mei (American Journal of Perinatology, 2020)
Objective The Baby-Friendly Hospital Initiative (BFHI) enables maternity units to be centers of breastfeeding support to increase breastfeeding rates. This study evaluates the impact of the 20-hour BFHI training course on nurses' breastfeeding knowledge, attitude, and confidence in breastfeeding practice in a tertiary hospital in Singapore.Study Design Seventeen sessions of the 20-hour BFHI training course were conducted by lactation consultants from 2010 to 2013 at the National University Hospital, Singapore. An anonymous self-administered survey on knowledge, attitude, and confidence in breastfeeding practices were distributed to nurses before (2009) and after (2014) the training courses to assess effectiveness of training.Results One-hundred forty nurses and one hundred forty-eight nurses participated in the surveys in 2009 and 2014, respectively. Majority were registered nurses who worked in the postnatal wards and the neonatal intensive care unit. After training, there were significant improvements for five of eight items in infant feeding knowledge, including greater awareness of the International Code of Marketing of Breastmilk Substitutes and medical contraindication for breastfeeding. Participants reported more confidence in assisting mothers on breastfeeding, 77.1 to 88.5% (p = 0.019); advising hand expressing breast milk, 75.7 to 86.5% (p = 0.012); and advising attachment to the breast, 75.7 to 89.2% (p = 0.004) in 2014 compared with 2009. However, despite having high levels of confidence, only about half the nurses reported being able to assist mothers in breastfeeding, mainly due to time constraints.Conclusion Implementation of the 20-hour BFHI training program positively influenced nurses' breastfeeding knowledge, attitude, and confidence in breastfeeding practices. Hospital procedures and manpower requirements should be re-examined to overcome nursing constraints in providing breastfeeding help to postpartum mothers.Key Points
Keywords: Baby-Friendly Hospital Initiative; nurses; education; breastfeeding; knowledge; attitude; confidence